Rampart of Health-Specific Leadership and Social Support of Colleagues to Overcome Burnout in an Emotionally Demanding Situations: The Mediating Role of Stress - Javaid MU; Rehman N; Mirza MZ; Ibrahim AM (Dove Medical Press, 2023)
Muhammad Umair Javaid,1 Nabeel Rehman,1 Muhammad Zeeshan Mirza,2 Aidarus Mohamed Ibrahim3 1Department of Management Sciences, Lahore Garrison University, Lahore, Pakistan; 2NUST Business School, National University of Sciences and Technology, Islamabad, Pakistan; 3College of Computing and IT, University of Hargeisa, Hargeisa, SomaliaCorrespondence: Aidarus Mohamed Ibrahim, Tel +252 636539717, Email aidarusibrahim11@gmail.com; aidarus.ibrahim@uoh.edu.soIntroduction: Past studies have neglected the role of resources that enhance motivation, such as health-specific leadership (H-SL) and social support colleagues (SSC), in dealing with the prerequisites of psychological health of workers, especially the duo of stress and burnout.Objective: This empirical study aimed to identify the impact of psychosocial job demands (emotional demands) and psychosocial job resources (health-specific leadership and social support of colleagues) on the psychological health (stress, burnout) of 284 Malaysian industrial workers (who participated both times).Methods: The Hierarchical regression analysis was employed to examine all study hypotheses and a time lagged study design was used with a lag of three months between T1 and T2 for data collection.Results: The survey data found a significant impact of emotional demands on stress and burnout, while we found insignificant findings of health-specific leadership and social support from colleagues on workers' psychological health.Future Directions: Future studies should consider the different formations of psychosocial job resources and higher dimensions of health promotion leadership.Keywords: emotional demands, health-specific leadership, stress, burnout, Malaysia